My First Prophet Muhammad Storybook - KHAN,SANIYASNAIN (UAE: Goodword, 2024)
Designed for use at home or at school, this book makes the message of the life of the Prophet Muhammad more meaningful for children. It$1 (Bs meant for 7 year olds and above, encourages children to discover for themselves the message of the life of the Prophet and to find their own ways of applying the Prophet$1 (Bs timeless teachings to their lives. These stories act as a foundation on which to build a growing knowledge of the life of the Prophet Muhammad.s